Current Conduction in Dual Channel Black Phosphorene Nanoribbon Transistor - Johari, Zaharah; Alias, Nurul Ezaila; Auzar, Zuriana (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Phosphorene continues to fascinate research community due to its excellent physical and electrical properties. In this paper, the feasibility study of using dual conducting channel in black phosphorene nanoribbon transistor is investigated using Atomistic simulation tool. Both electronic and transport properties are evaluated. Through simulation, it is demonstrated that the conduction behavior behave differently where the current exhibit a great deal of increment when using dual channel. The performance was superior compared to single channel and suggests that the number of conducting channel is a significant factor in improving device behavior.